Implementation of Face-to-Face Model in The Learning of Islamic Education During the Covid-19 Pandemic in Mts. Nurul Mannan Jember. - Ahmad Halid; Sakinatus Saniyyah (Educan : Jurnal Pendidikan Islam, 2022)
This study aims to determine the effectiveness of periodic face-to-face learning carried out during the COVID-19 pandemic as a way out of the ineffectiveness of online learning conducted previously in MTs. Nurul Mannan, Sukogidri Village, Ledokombo District, Jember Regency. And the research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the regular face-to-face strategy is effective as an option for madrasas whose facilities and infrastructure do not support online learning, of course, while still complying with the health protocols recommended by the government.Of course, it is balanced with the efforts of educators in choosing the right method in order to achieve the desired learning objectives.